FOREIGN INTERVENTION IN AFRICA: FROM THE COLD WAR TO THE WAR ON - Shubin, Vladimir (Scientia Militaria - South African Journal of Military Studies, 2014)
This book by Elizabeth Schmidt, Professor of History at Loyola University Maryland, was published in the series New Approaches to Africa History, designed to introduce students to current findings and new ideas on the history of the continent. This approach affected the mode of presentation, but did not prevent the book from being a profound and pioneering academic work.